Sustained efficacy of artesunate-sulfadoxine-pyrimethamine against Plasmodium falciparum in Yemen and a renewed call for an adjunct single dose primaquine to clear gametocytes. (December 2016) - Atroosh, Wahib; Al-Mekhlafi, Hesham; Snounou, Georges; Al-Jasari, Adel; Sady, Hany; Nasr, Nabil; Lau, Yee-Ling; Surin, Johari
Abstract Background In Yemen, artesunate plus sulfadoxine-pyrimethamine (AS + SP) has been used as first-line treatment for uncomplicated falciparum malaria, which accounts for about 99 % of malaria cases. There is evidence that resistance to SP is increasing, with potential negative impact on efficacy, and in particular on curbing transmission. This study aims: (a) to evaluate the therapeutic efficacy of AS + SP treatment for uncomplicated falciparum malaria in Yemen; (b) to investigate the frequency of mutations inPlasmodium falciparum genes associated with resistance to AS (Kelch 13 propeller domain, pfK13 ) and SP (dihydrofolate reductase, pfdhfr, and dihydropteroate synthase, pfdhps ); and (c) to assess the adequacy of this ACT to clear gametocytes. Methods A 28-day in vivo evaluation of the clinical and parasitological response to three-day course of AS + SP was carried out in two areas of high endemicity (Hodeidah and Al-Mahwit provinces, Tehama region) in Yemen according to standard WHO protocol 2009. Clinical and parasitological indices were monitored over a 28-day follow-up, and the outcome was PCR-corrected. The frequencies of mutations in thepfdhfr, pfdhps, andpfK13 genes were obtained by sequencing following amplification. Results Eighty-six patients completed the study, with a cure rate of 96.5 % (94.2 % PCR-uncorrected). Whereas four (4.7 %) patients still showed parasitaemia on day 2 post-treatment, all were found negative for asexual malaria stages on days 3 and 7. The efficacy of gametocyte clearance was poor (14.5, 42.5 and 86.0 % on days 7, 14 and 28, respectively), with gametocytes persisting throughout the study in some patients. All the isolates sequenced had thepfk13 propeller domain wild-type allele, and mutations associated with SP failure were observed only forpfdhfr with the double mutation (S108N + N51I) found in 65.4 % of the isolates sequenced. Conclusion In Yemen, AS + SP therapy remains effective for the treatment of uncomplicated falciparum malaria. Mutations were not detected inpfk13 orpfdhps, though double mutations were observed forpfdhfr . The observed persistent gametocytaemia re-enforces calls to add a single dose primaquine to this ACT in order to minimizes the potential for transmission and enhance regional efforts to eliminate malaria.